Rsac on the Influence of Social Media Content on Teenager Behaviors in the Internet Era - Zhang, Pu (Transactions on Social Science, Education and Humanities Research, 2024)
Human beings invented the Internet in the late 20th century, which made communication between people faster as well as easier. With the evolution of the Internet, social media has gradually begun to develop since the 21st century. Today, social media has evolved and has a significant impact on the human race. The majority of users are teenagers. As the future of the world, the development of teenagers is especially important. Therefore, this thesis analyzes the influence of content on social media on teenagers’ behavior. The thesis adopts the literature research method to analyze the influence of three common contents of social media on teenagers, which are memes, trending videos, and pranks. Finally, the author discusses and analyzes the effects of these three types of content on adolescent behavior and the multifaceted results of these effects. This study finds that social media affects adolescents’ behavior, and the three most significant categories of content are memes, trending videos, and pranks.